Integration of Service Quality Method (SERVQUAL) and Lean Concept to Improve Service Quality: Case Study in Medical Center of ITS: Integrasi Service Quality (SERVQUAL) dan Konsep Lean untuk Meningkatkan Kualitas Layanan: Studi Kasus pada UPT Medical Center ITS - Pratiwi, Atikah Aghdhi; Nabilah, Isnaini Mutiara; Wessiani, Naning Aranti (Universitas Muhammadiyah Sidoarjo, 2025)
The government is responsible for ensuring the right to health, one of its efforts is the Healthy Campus program. This initiative underpins the establishment of the ITS Medical Center at Institut Teknologi Sepuluh Nopember (ITS) to fulfill students' rights to healthcare services. ITS Medical Center aims to become the leading healthcare service provider for the ITS academic community and the public in East Surabaya. However, numerous complaints persist, with 50% related to extended service waiting times. Additionally, ITS Medical Center experienced an 11% increase in visitors in 2023. Consequently, a service quality evaluation was conducted by integrating Service Quality (SERVQUAL) and lean concepts to identify service gaps, eliminate waste, and enhance services. The study revealed negative results across all SERVQUAL attributes. Out of 24 identified wastes, 17 were deemed critical. These critical wastes and their associated attributes were grouped and analyzed for root causes using Fault-Tree Analysis. The prioritized wastes include patients waiting for medication preparation, the reprocessing of old patient medical records, and the excessive accumulation of medical records. Recommendations for improvement prioritize recording dispensed medications in stock cards at the end of the day and developing a system for medical record recapitulation. These improvements are expected to enhance service quality and increase consumer satisfaction at the ITS Medical Center.